The Effect of SAVI Learning Model on Students' Critical Thinking Skills - Fera Lindra Ismawanti; Mohamad Nur; Leny Yuanita (IJORER : International Journal of Recent Educational Research, 2022)
This research aims to determine the effect of the SAVI learning model on the critical thinking skills of junior high school students. The method used in this research is one group pre-test-post test, with a descriptive quantitative approach. The test is done online via a google form. The question instrument contains 10 multiple choice questions and 5 questions on the description of the digestive system material that has been validated by the validator. This study involved 90 students of grade 8. The results showed that the validation results of critical thinking test questions obtained a mode 4 score and a reliability value of 86%, while the results of the students' critical thinking skills test showed that after the SAVI learning model was applied there was an increase obtained from the average pretest score of 40 and the average score The post-test average was 81 so that the N-gain score increased by 0.68 in the medium category, and all critical thinking indicators were achieved well.